Alternaciones funcionales y moleculares producto de la administración combinada de cocaína y cafeína en un modelo murino - Muñiz, Javier Andrés (2019)
An important challenge for the neurobiology of drug abuse is to understand the neuroadaptive \ndifferences between controlled drug use and loss of control. Caffeine is the most popular \npsychoactive drug in the world and is also an active adulterant found in many drugs of abuse, \nincluding seized samples of cocaine. Our results show that the intake of both caffeine and \ncocaine produces locomotor sensitization and astrogliosis in the striatum, prefrontal and \nmotor cortex after chronic treatment, in addition to changes in gene expression, directed to \ndopamine, adenosine and glutamate receptor subunits. At peripheral organs, the results of \nthese studies provide evidence of hepatotoxicity and decreased levels of TH and gene \nexpression of neurotransmitter receptors in the testis. Using the place preference conditioning \ntest (CPP), the combination of drugs induced a marked change in preference and a significant \nincrease in locomotion compared to cocaine alone. Gene expression analysis after the CPP test \nrevealed a specific increase of several immediate early genes in the mice that received the \ncombination of cocaine and caffeine. These data suggest specific neuroplastic changes in mice \nreceiving the combination of both psychostimulants that are area-dependent and context\nrelated.